Vloga in odgovornost projektanta pri projektiranju enostanovanjske stavbe in gradnji v lastni režiji - Klemenčič Manič, Mojca (IB revija (Ljubljana), 2012)
This paper analyses the role and importance of a house designer and his controlling bodies in the project of building a single-family house and in a home-construction building practice. We studied the responsibility of professional participants in practices that must be consistent both with the legal and the ethical-moral rules of corporate social responsibility. Regarding the house designer's responsibility in the project process, we are particularly interested in the findings of his supervision bodies, i.e. professional associations (Slovenian Chamber of Architecture and Spatial Planning and Slovenian Chamber of Engineers), as well as the findings of the building inspectorate in the building practice. The Construction Act and the rules are specifying the professional participants' obligations in the project process and providing enforcement penalties are critically analysed. In this process, different interests are represented, and the legislation must (in terms of institutional quality and socially responsible behaviour of institutions involved) ensure the minimum standards in preparing high quality project documentation, which is crucial for a safe and reliable building construction process and for living in the single-family houses.
Keywords: buildiing inspection; building practice; delovanje inštitucij; družbena odgovornost; gradbena inšpekcija; gradnja; house designers; institutional quality; kakovost; projects; projects documentation; projektanti; projekti; projektna dokumentacija; social responsibility